"They call me anneanne!" translanguaging as a theoretical and pedagogical challenge and opportunity in the kindergarten context in Norway. (2nd January 2021) - Pesch, Anja Maria
ABSTRACT: Translanguaging has become a popular concept in educational contexts. However, it has not been discussed much in the kindergarten context of Norway. Many studies on translanguaging have been carried out in specific bilingual classrooms. In kindergartens in Norway, Norwegian is usually the common and majority language whilst a growing number of children attending kindergarten are multilingual with diverse linguistic background, and kindergarten teachers often have limited knowledge in the children's languages. The article elaborates on the concept of translanguaging from an educational and linguistic perspective. The concept of translanguaging is used as a theoretical lens to discuss kindergarten teachers' pedagogical practice with multilingual children and parents, as well as discourses in the kindergarten curriculum. The subsequent discussion focuses on the challenges and possibilities that translanguaging brings in its encounter with the kindergarten context in Norway. Whilst translanguaging may bring important challenges on existing views on language and multilingualism and create heteroglossic linguistic spaces for communication with children and their parents, it also encounters boundaries in the complex communication reality in kindergartens in Norway.